2019
DOI: 10.1007/s00191-019-00609-y
|View full text |Cite
|
Sign up to set email alerts
|

More is different ... and complex! the case for agent-based macroeconomics

Abstract: This work nests the Agent-Based macroeconomic perspective into the earlier history of macroeconomics. We discuss how the discipline in the 70's took a perverse path relying on models grounded on fictitious rational representative agent in order to try to pathetically circumvent aggregation and coordination problems. The Great Recession was a natural experiment for macroeconomics, showing the inadequacy of the predominant theoretical framework grounded on DSGE models. After discussing the pathological fallacies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(45 citation statements)
references
References 229 publications
0
27
0
2
Order By: Relevance
“…7 Agent-based macroeconomic models have received increasing attention in the recent literature. Compare for instance a recently published special issue edited byDosi and Roventini (2019), also featuring a macro ABM with endogenous social class dynamics as discussed previously (Rengs and Scholz-Wäckerle 2019). 8 Brackets added by the authors.…”
mentioning
confidence: 99%
“…7 Agent-based macroeconomic models have received increasing attention in the recent literature. Compare for instance a recently published special issue edited byDosi and Roventini (2019), also featuring a macro ABM with endogenous social class dynamics as discussed previously (Rengs and Scholz-Wäckerle 2019). 8 Brackets added by the authors.…”
mentioning
confidence: 99%
“…In addition to the area of engineering optimisation problems, the field of industrial economics is also very popular. In 2019, Dosi et al introduced a comprehensive theoretical survey of the history of agent-based macroeconomics [3]. The authors critically discussed the issues found in macroeconomics from different points of view.…”
Section: Introductionmentioning
confidence: 99%
“…We rely in our analysis on an agent-based modeling approach, which has become a widely used approach for studying issues related to innovation and industrial dynamics from an evolutionary perspective, see, e.g. Nelson and Winter (1982); Dosi et al (1995); Landini et al (2017); Dawid et al (2019), or the survey in Dawid (2006), as well as in labor economics (Neugart and Richiardi, 2018), and macroeconomics (Dawid and Delli Gatti, 2018;Dosi and Roventini, 2019). Several recent contributions have studied different implications of automation using an agent-based approach.…”
Section: Introductionmentioning
confidence: 99%